The rise of deferred tax assets in Japan: The role of deferred tax accounting in the Japanese banking crisis - Skinner, Douglas J. (Journal of Accounting and Economics, 2008)
This paper provides evidence on the role of deferred taxes in the recent financial crisis among Japanese banks. Upon adoption of deferred tax accounting in FY1998, the major Japanese banks recognized net deferred tax assets of ¥6.6 trillion ($55 billion). Without these assets, the banks would have been insolvent. The evidence supports the conclusion that Japanese regulators used deferred tax accounting as part of a regulatory forbearance strategy, and that bank managers used these assets to bolster their banks’ regulatory capital. The results show how ostensibly similar accounting rules can be implemented very differently, and so have implications for IFRS.